2009
DOI: 10.1007/s10557-009-6168-5
|View full text |Cite
|
Sign up to set email alerts
|

Remote Postconditioning is More Potent than Classic Postconditioning in Reducing the Infarct Size in Anesthetized Rabbits

Abstract: Remote postconditioning consisted of 1 min isc/1 min rep protects the ischemic rabbit heart in vivo, independently of the site of the remote artery. This intervention seems to confer a stronger protection than the classic postconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 21 publications
0
41
0
1
Order By: Relevance
“…Of note, uremic animals treated with RIPC fared no better than their shamoperated counterparts. It is interesting to compare these results with those of Gritsopoulos et al, 38 who found that remote postconditioning was a more potent cytoprotective strategy than classic postconditioning, suggesting that further direct interference with the dependent vascular bed, which had experienced the index ischemic episode, was not entirely without consequence.…”
Section: Discussionmentioning
confidence: 68%
“…Of note, uremic animals treated with RIPC fared no better than their shamoperated counterparts. It is interesting to compare these results with those of Gritsopoulos et al, 38 who found that remote postconditioning was a more potent cytoprotective strategy than classic postconditioning, suggesting that further direct interference with the dependent vascular bed, which had experienced the index ischemic episode, was not entirely without consequence.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, the remote ischemic conditioning procedure can be applied before and during sustained ischemia 76 and at the onset of reperfusion. 77 An experimental study showed that the infarct-size-limiting effects 78 It remains unclear how remote ischemic conditioning exerts cardioprotection; however, 2 major hypotheses have been proposed (Figure 3). The neural hypothesis states that autacoids released from the ischemic remote organ affect the local afferent neural pathway, which in turn, activates the efferent neural pathways to trigger endorgan protection.…”
Section: Remote Ischemic Conditioningmentioning
confidence: 99%
“…7 Clinically, postconditioning is achieved by repeated inflation and deflation of the angioplasty balloon after emergency coronary intervention. 8 It is now known that postconditioning can be induced experimentally and in humans, remotely, using a transient limb ischemia stimulus identical to that of remote pre-and preconditioning, and in a recent study, remote postconditioning was more effective than local postconditioning in experimental MI 9 . We have shown that repeated daily remote conditioning by limb ischemia leads to significant downregulation of neutrophil activation and proinflammatory responses in humans.…”
mentioning
confidence: 99%